Hepatoprotective activity of phloretin and hydroxychalcones against Acetaminophen Induced hepatotoxicity in mice - Ali Reza Ebadollahi Natanzi; Shima Mahmoudian; Bagher Minaeie; Omid Sabzevari (Iranian Journal of Pharmaceutical Sciences, 2011)
Polyphenolics form a major part of the dietary antioxidant capacity of fruits and vegetables have been identified as chemopreventive or anticancer agents. Hydroxychalcones are polyphenols abundantly distributed throughout the plant kingdom and are compounds with two aromatic rings (benzene or phenol) and an unsaturated side chain. In the present study, effect of phloretin (apple major flavonoid), 4-hydroxychalcone and 4'-hydroxychalcone were investigated against acetaminophen-induced acute liver damage. The study was designed as multiple dose pre- and post-treatments. Mice were administrated acetaminophen (1g/kg and 640 mg/kg for mortality and acute toxicity experiments, respectively). Mortality rate, serum transaminases (SGOT and SGPT) and histological examination were applied. Acetaminophen produced 100% mortality at the dose of 1 g/kg in mice, while pre-treatment and post-treatment (i.p., twice daily for 48 hrs) of animals with phloretin and 4-hydroxychalcone (50 mg/kg) and 4'-hydroxychalcone (25 mg/kg) significantly reduced the mortality rate. Acetaminophen produced acute toxicity at the dose of 640 mg/kg in mice, while pre- and post-treatments of animals with phloretin and hydroxychalcones significantly lowered the rise in SGOT and SGPT. Liver sections collected for histological examination showed cellular changes including centrilobular necrosis, extensive portal inflammation, and micro and macro vesicular structures in the acetaminophen group. These cellular changes were reduced following treatment of mice with Phloretin and hydroxychalcones. Taken collectively, from the results of this study it may be suggested that phloretin and hydroxychalcones have hepatoprotective activity against acetaminophen liver injury in mice.